Effects of phase angle setting, displacement, and eccentricity ratio based on determination of rhombic-drive primary geometrical parameters in beta-configuration Stirling engine - Mohd Farid, Zainudin; R. A., Bakar; K., Kadirgama (IOP Publishing, 2019)
Stirling engine is an external combustion engine, which generates power from any kind of heat source. Stirling engine offers lower emissions level compared to the internal combustion engines. The driving mechanisms differ based on the engine configurations. For beta-configuration Stirling engine, rhombic-drive mechanism indicates most suitable driving mechanism due to the concentric cylinder’s arrangement. The determination of rhombic-drives primary geometrical parameters and consideration from various aspects are needed to achieve high power production, efficiency and ensure successful engine operation. In this paper, the kinematic investigations of rhombic-drives primary geometrical parameters are carried out to investigate the effects of phase angle, displacement and eccentricity ratio based on predetermination of different crank offset radius, eccentricity ratio and connecting rod length. It is found that the adjustment of crank offset radius cause significant effect to the eccentricity ratio and engines displacement. Meanwhile, the adjustment of connecting rod length induced significant changes in phase angle since there are changes in TDC and BDC for both pistons.